Method of Nonperturbing Measurements of the Electron Bunch Length Based on Coherent Diffraction Radiation; Physics of Particles and Nuclei Letters; Vol. 18, iss. 2 - Popov K. E. Konstantin Evgenjevich; Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Shevelev M. V. Mihail Viktorovich; Shkitov D. A. Dmitriy Andreevich; Popov Yu. A. Yuriy Anatolevich (2021, 2021)
Title screen